IgA-Targeted Lactobacillus jensenii Modulated Gut Barrier and Microbiota in High-Fat Diet-Fed Mice - Sun, Jin; Qi, Ce; Zhu, Hualing; Zhou, Qin; Xiao, Hang; Le, Guowei; Chen, Daozhen; Yu, Renqiang (Frontiers in Microbiology, 2019)
IgA-coated Lactobacillus live in the mucous layer of the human or mammalian intestine in close proximity to epithelial cells. They act as potential probiotics for functional food development, but their physiological regulation has not yet been studied. We isolated IgA-targeted (Lactobacillus jensenii IgA21) and lumen lactic acid bacterial strains (Pediococcus acidilactici FS1) from the fecal microbiota of a healthy woman. C57BL/6 mice were fed a normal (CON) or high fat diet (HFD) for 6 weeks and then treated with IgA21 or FS1 for 4 weeks. HFD caused dyslipidemia, mucosal barrier damage, and intestinal microbiota abnormalities. Only IgA21 significantly inhibited dyslipidemia and gut barrier damage. This was related to significant up-regulation of mucin-2, PIgR mRNA expression, and colonic butyrate production (P<0.05 vs HFD). Unlike IgA21, FS1 caused a more pronounced gut dybiosis than did HFD, and, in particular, it induced a significant decrease in the Bacteroidales S24-7 group and an increase in Desulfovibrionaceae (P<0.05 vs CON). In conclusion, IgA-coated and non-coated lactic acid bacteria of gut have been demonstrated to differentially affect the intestinal barrier and serum lipids. This indicates that IgA-bound bacteria possess the potential to more easily interact with the host gut to regulate homeostasis.